The Unified Continental Approach to the Mpox Outbreak Preparedness and Response: A Model for Future Outbreaks in Africa - Ngashi Ngongo; Nicaise Ndembi; Mosoka Fallah; Wessam Mankoula; Merawi A. Tegegne; Moréniké Oluwátóyìn Foláyan; Jean Kaseya (Journal of Public Health in Africa)
No abstract available.